The Analysis of the Sepak Rago Tinggi Traditional Game in Kenegerian Kopah Community - Wulandari , Nova Reza; Daryusti (Universitas Jambi, Indonesia, 2023)
Sepak Rago Tinggi is a traditional game of the Kenegerian Kopah community, Kuantan Singing Regency, which has existed since the ancient times. This research aimed to reveal the Sepak Rago Tinggi traditional game. This research used qualitative with a descriptive approach. The research object was the Sepak Rago Tinggi traditional game in the Nigerian Kopah community, Kuantan Singing Regency. The data used were primary data and secondary data. In addition, this research used observation and documents to collect data. Meanwhile, the data analysis techniques combined all data obtained, checked, and filtered until the data became valid. The results of this research indicated that the forms of the traditional game of Sepak Rago Tinggi in the Kenegerian Kopah, Kuantan Singing Regency was a game against crime that was previously played by traditional leaders consisting of representatives from each tribe in the Kenegerian Kopah. Sepak Rago Tinggi is played by using the umbrella property, in which the umbrella is the target into which the Rago ball is placed.